Association between mental health status and bone mineral density: Analysis of the 2008-2010 Korea national health and nutrition examination survey - Hahn, Changtae (PLoS One, 2017)
The current study aimed to investigate the association between mental health status and bone mineral density (BMD) using data from the Korean National Health and Nutrition Examination Survey (KNHANES) 2008–2010. We enrolled 15,876 South Korean participants (4,010 postmenopausal females, 4,836 premenopausal females, and 7,016 males, all aged 20 years or older). BMD was measured using dual-energy radiography absorptiometry at the femoral neck (NK), lumbar spine (LSP), and total femur (TFM). Mental health status data were obtained from a self-report questionnaire that assessed psychological stress, depressed mood, and suicidal ideation. Psychological stress was negatively correlated with BMD in the LSP, NK, and TFM for the male group. Depressed mood was associated with lower BMD in the LSP, NK and TFM for the premenopausal female group, and in the LSP for the male group. Suicidal ideation was associated with lower BMD in the NK and TFM for the male group. Mental health problems were associated with lower BMD, especially in premenopausal females and males. Future investigations should focus on the shared pathophysiology between mental health problems and BMD, and the interrelationship between increased BMD and recovery from mental health problems.